Poultry Response to Heat Stress: Its Physiological, Metabolic, and Genetic Implications on Meat Production and Quality Including Strategies to Improve Broiler Production in a Warming World - Nawaz, Ali H.; Amoah, Kwaku; Leng, Qi Y.; Zheng, Jia H.; Zhang, Wei L.; Zhang, Li (Frontiers in Veterinary Science, 2021)
The continuous increase in poultry production over the last decades to meet the high growing demand and provide food security has attracted much concern due to the recent negative impacts of the most challenging environmental stressor, heat stress (HS), on birds. The poultry industry has responded by adopting different environmental strategies such as the use of environmentally controlled sheds and modern ventilation systems. However, such strategies are not long-term solutions and it cost so much for farmers to practice. The detrimental effects of HS include the reduction in growth, deterioration of meat quality as it reduces water-holding capacity (WHC), pH and increases drip loss in meat consequently changing the normal color, taste and texture of chicken meat. HS causes poor meat quality by impairing protein synthesis and augmenting undesirable fat in meat. Studies previously conducted show that HS negatively affects the skeletal muscle growth and development by changing its effects on myogenic regulatory factors (MRFs), insulin growth factor-1, and heat-shock proteins. The focus of this article is in threefold: (1) to identify the mechanism of heat stress that causes meat production and quality loss in chicken; (2) to discuss the physiological, metabolic and genetic changes triggered by HS causing setback to the world poultry industry; (3) to identify the research gaps to be addressed in future studies.